Causas, efectos y costos de la corrupción en el Perú - Romero Antola, Mario (2022)
This work analyzes the causes, effects and costs of corruption in Peru, seeking to know and understand more about this phenomenon, cause-effect of our underdevelopment, with the fundamental objective of contributing to its understanding and perceiving the harmful effects for Peruvian society and its high economic and moral costs, in order to try to combat it more efficiently and effectively.